Ø§Ù„Ù†ØØª Ø§Ù„Ù…Ø¹Ø§ØµØ± ÙˆØ§Ø³ØªÙØ§Ø¯ØªÙ‡ ÙÙŠ ØªÙ†Ù…ÙŠØ© Ø§ÙƒØªØ³Ø§Ø¨ Ù…ÙØ±Ø¯Ø§Øª Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø¨Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§ - Sugeng Ali Mansur; Shofil Fikri (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan UIN Saizu Purwokerto, 2022)
Sculpture is a famous word that many students did not know in high schools in Indonesia, but it was used by the Arabs sometimes, and the Indonesians also used it in communication in this modern era. This research is important to know sculpture in general and to know contemporary sculpture in the Arabic language, and to suggest the teacher's attempts to benefit from contemporary sculpture in developing vocabulary acquisition for high school students in Indonesia. This qualitative research used the descriptive method with the help of books, scientific articles and other library aids. The results of the research: 1) knowledge of the concept of sculpture in general 2) the concept of contemporary sculpture, 3) suggestions for the teacher to benefit from contemporary sculpture in developing vocabulary acquisition for high school students in Indonesia are three: (1) The teacher prepares exercises brochures that include new vocabulary from sculpture Contemporary increase an accompanying addition to the books of the prescribed basic educational materials; (2) The teacher provides students with the opportunity to follow the Arabic language program on TV and the Internet to research new terms from contemporary sculpture; (3) The teacher gives the students the opportunity to watch Arab cinema together during the teaching process.